The Use of Primates as Experimental Models in Scientific Research and its Ethical Implications - , Flávia Aparecida de Oliveira Bezerra, José Sérgio Herculano Gomes da Silva, Elton Santos Guedes de Morais, Mariza Brandão Palma, Anísio Francisco Soares (Archives of Current Research International, 2024)
Non-human primates (NHPs) are considered ideal experimental models for replicating human diseases, due to their physiological, anatomical and neurological similarities to humans. However, the use of NHPs in research has ethical considerations and requires significant financial and temporal investments, due to the costs involved in the process and evaluation time. In addition to ethical issues and legal protection, research with experimental primate models involves advantages, such as the extreme physiological similarity, and disadvantages, such as the difficulty in establishing parameters for pain management and assessment. This literature review analyzed articles from the Pubmed, Scopus and Web of Science databases published in the last five years. This review included 12 articles that addressed topics such as scientific research, primate therapies, animal welfare and legal protection, highlighting the relevance of NHPs in scientific studies and interest in using these models to understand human diseases in order to develop new therapies. Despite the ethical challenges involved in this issue, it was discussed that it is important to take into account the scientific benefits and ethical considerations, as well as developing alternative methods to reduce the use of primates in research.